Pengaruh Teknologi Informasi, Partisipasi Manajemen, Kemampuan Pemakai SIA, Pendidikan dan Pelatihan pada Kinerja Manajemen LPD - Pradasari, Ni Komang Diana; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p14, 2018)
This study aims to determine the effect of information technology, participation on management, user capabilities SIA, educationan and training of management performance LPD. This research was conducted at 35 LPD in Denpasar. The sample used in this study amounted to 35 LPD so that the total sample used amounted to 105 respondents by using purposive sampling method as the method of determining the sample. Data collection method used in this research using questionnaires. Data analysis technique used is multiple linear regression. Based on the analysis result, it is found that information technology, the participation on management, user capabilities SIA, educationan and training have positive effect on LPD management performance in Denpasar. Keywords : information technology, participation on management, user capabilities SIA, educationan and training, management performance LPD